1978
DOI: 10.1139/o78-175
|View full text |Cite
|
Sign up to set email alerts
|

Horseradish peroxidase. XXXII. pH dependence of the oxidation of L-(−)-tyrosine by compound I

Abstract: The rate of oxidation of L-(-)-tyrosine by horseradish peroxidase compound 1 has been studied as a function of pH at 25 degrees C and ionic strength 0.11. Over the pH range of 3.20--11.23 major effects of three ionizations were observed. The pKa values of the phenolic (pKa = 10.10) and amino (pKa = 9.21) dissociations of tyrosine and a single enzyme ionization (pKa = 5.42) were determined from nonlinear least squares analysis of the log rate versus pH profile. It was noted that the less acidic form of the enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…5 (28,29). CpdI can promote the formation of two tyrosyl radicals, as demonstrated with the horseradish peroxidase, another hemecontaining protein forming CpdI as the reactive species (30,31). Moreover, one of the major reactions observed between two tyrosyl radicals is the formation of a tyrosyl cross link between the carbon atoms positioned ortho with respect to the hydroxyl (32).…”
Section: Discussionmentioning
confidence: 96%
“…5 (28,29). CpdI can promote the formation of two tyrosyl radicals, as demonstrated with the horseradish peroxidase, another hemecontaining protein forming CpdI as the reactive species (30,31). Moreover, one of the major reactions observed between two tyrosyl radicals is the formation of a tyrosyl cross link between the carbon atoms positioned ortho with respect to the hydroxyl (32).…”
Section: Discussionmentioning
confidence: 96%
“…4). Tyrosine is oxidized by horseradish peroxidase compound I at a rate of 5.0 ϫ 10 4 M Ϫ1 s Ϫ1 (19) and compound II at a rate of 1.1 ϫ 10 3 M Ϫ1 s Ϫ1 (20). The observed tyrosyl radical ESR spectrum (Fig.…”
Section: Figmentioning
confidence: 96%
“…A second ionization with a pK, of 9.16 corresponding to the amino group of tyrosine, results in a large decrease in k,,,,,. The opposite effect was noted for the oxidation of tyrosine by compound I where the rate increased with deprotonation of the ainino moiety (29). Since it has been found that dityrosine (linked at the ortho positions) is the favoured reaction product for the hydrogen peroxide oxidation of tyrosine ( 4 0 ) , it seems unlikely that electron (or hyd;ogen atom) transfer would occur at the aliphatic side chain.…”
Section: Reaction O F Cornpound I I With Diiodotyrosinementioning
confidence: 96%